Gender Roles and Representation in A Multilingual Children’s Book: An Anthology of Indonesian Children’s Stories - Ahmad, Ahmad; Susanto, Ashabul Kahfi (Lexicon, 2024)
All children should be able to see themselves reflected in the books they read. However, in some children’s books, male and female characters are not always equally represented. When these characters are included, it is important to see how they are portrayed. This study aims to examine gender representation in An Anthology of Indonesian Children’s Stories published by The Agency for Language Development and Cultivation, The Ministry of Education, Culture, Research and Technology in 2022, by focusing on revealing two aspects. The first involves comparing the ratio of male and female protagonists, as well as other characters, using the quantitative method. The second focuses on examining the portrayal of gender roles among the protagonist characters using the qualitative method. The findings show that male protagonists outnumber female protagonists by a ratio of 7:3. However, although only three out of ten stories have three female protagonists, they are represented as having progressive gender roles: adventurous and empowered. In addition, certain stories appear to reinforce traditional gender roles. Yet, they also portray the cultural values of “Gotong Royong” which promote cooperation within family: men and women have their own responsibilities to support their communities.